2011
DOI: 10.1038/cmi.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of cell proliferation and inhibition of ADCC by cancerous immunoglobulin expressed in cancer cell lines

Abstract: To explore the significance of cancerous immunoglobulin (Ig) in cancer cell growth, HeLa cervical cancer cells were stably transfected with small interfering RNA (siRNA) that specifically, efficiently and consistently silences the expression of heavy chain genes of all immunoglobulin isotypes. This stable cell line was used to examine cell viability, colony formation and tumor growth in athymic nude mice. The results of these experiments indicated that siRNA-mediated knockdown of cancerous Ig inhibited cell gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 14 publications
5
61
0
1
Order By: Relevance
“…15,23 Li et al found that cancerous immunoglobulin promoted cell proliferation and inhibited antibody-dependent cell-mediated cytotoxicity. 26 It is possible that hepatocyte-produced IgG acts as a growth factor to participate in signaling pathways, leading to cell proliferation and apoptosis in normal hepatocytes and hepatocarcinomas. Therefore, hepatocyte-produced Ig may also affect liver transplant, regeneration and repair.…”
Section: Discussionmentioning
confidence: 99%
“…15,23 Li et al found that cancerous immunoglobulin promoted cell proliferation and inhibited antibody-dependent cell-mediated cytotoxicity. 26 It is possible that hepatocyte-produced IgG acts as a growth factor to participate in signaling pathways, leading to cell proliferation and apoptosis in normal hepatocytes and hepatocarcinomas. Therefore, hepatocyte-produced Ig may also affect liver transplant, regeneration and repair.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Furthermore, non-hematopoietic cellderived Ig has a role in cell growth and survival. 1,3,15,16 These findings suggest that Ig derived from non-hematopoietic cells might be a novel molecule with a unique structure and function and might play a role in carcinogenesis and/or tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Among the serum proteins or fragments detected by LC-MS/MS, more than half were found to be relevant to the growth/proliferation or inhibition of cancer cells in vitro or in vivo, as demonstrated by other researchers (M. Li et al, 2004;M. Li et al, 2012;Qiu et al, 2003).…”
Section: Biochemical and Immunological Characterizations Of Ca215-s+mentioning
confidence: 74%
“…Previous studies have indicated that through binding to the RP215-specific epitope in CA215 on the surface of cultured cancer cells, apoptosis was induced as judged by using the TUNEL assay method (Chen & Gu, 2007;Lee et al, 2010;Lee & Ge, 2010;Lee, Cheung, Ge, et al, 2012;M. Li et al, 2012;Qiu et al, 2003;.…”
Section: Apoptosis Experimentsmentioning
confidence: 99%
See 1 more Smart Citation